Cultural Differences and Marketing Success - Behrman, Jack N. (Marketing & Menedzsment, 2019)
A major problem facing business dealing internationally is the need to become more sensitive to foreign cultures. There are numerous stories of the "blunders" in marketing as a result of companies thinking that the foreigner's "mind-set" was similar to their own - both as marketers and consumers. Such blunders are even more important in cross-cultural management in the various partnerships and production facilities located abroad. Managers in no country have shown pervasive ability or willingness to learn about or adjust to the management styles or cultures in other countries - despite, or because of, long colonial attitudes.